Commentary on: "effects of motor imagery-based neurofeedback training after bilateral repetitive transcranial magnetic stimulation on post-stroke upper limb motor function: an exploratory crossover clinical trial" - Anjali Raghuwanshi; Saliha Rafat; Adarsh Kumar Srivastav (Medical Journals Sweden, 2024)
Abstract is missing (Commentary)